Carbonyl ruthenium catalysts for the low-temperature water–gas shift reaction with ionic liquids as support structure controllers. Issue 17 (1st June 2016) - Zhang, Yingchao; Zuo, Cuncun; Li, Chunshan; Guo, Xinpeng; Zhang, Suojiang
Abstract : The performance of the Ru/IL@SiO2 catalysts in the WGS reaction was evaluated. Different IL structures can strongly affect the pore structure of the catalyst support, actual Ru content, and CO adsorption capacity thereby considerably affecting the activity and stability of the catalysts. Abstract : A series of SiO2 -confined Ru3 (CO)12 catalysts for the water–gas shift (WGS) reaction was synthesized using a sol–gel method with five different 1-butyl-2, 3-dimethylimidazolium ionic liquids (ILs) with BF4 −, NO3 −, Cl −, OTf −, and NTf2 − . FT-IR, XRD, BET, SEM/EDS, TEM, ICP, CO-TPD and TGA were used to determine the influence of the different IL structures and loadings (10–40%) on the structure of the synthesized silica gel, Ru dispersion, and WGS catalytic activity. The results revealed that hydrogen bond formation capability and size of the anion of ILs have significant and sensitive effects. Catalytic activity was tested at atmospheric pressure and low reaction temperatures ranging from 120 to 200 °C. The highest CO conversion of 93.7% was achieved at 160 °C, which showed an around 100 °C decrease compared to traditional catalysts.